Perioperative dexamethasone in high-grade gliomas: the short-term benefits and long-term harms - Mistry, Akshitkumar M. (Frontiers in Oncology, 2023)
Dexamethasone has been commonly given to patients with a presumed new GBM in relatively large doses (6-16 mg daily for 1-2 weeks) since the 1960s without any rigorous evidence. This treatment with dexamethasone before the diagnosis and adjuvant therapy makes GBM patients unique compared to other newly diagnosed cancer patients. While dexamethasone may be beneficial, recent studies suggest that this potent immunosuppressant with pleiotropic effects is harmful in the long term. This perspective article summarizes the disadvantages of perioperative dexamethasone from multiple facets. It concludes that these growing data mandate rigorously testing the benefits of using perioperative dexamethasone.